Atomic-level finishing of aluminum alloy by chemo-mechanical magneto-rheological finishing (CMMRF) for optical applications. (April 2018) - Ghai, Viney; Ranjan, Prabhat; Batish, Ajay; Singh, Harpreet
Highlights: Al alloy 7075-T6 was finished with newly developed hybrid process chemo-mechanical magneto-rheological finishing (CMMRF) for primary metal mirror in optical telescopes best results found were surface roughness value of 5.97 Å. CMMRF process minimum surface roughness value for aluminium achieved was 0.597 nm, which was 60% better than Diamond turn machining (DTM) and 66.6% better than Chemo-mechanical polishing (CMP) process. Finishing of aluminium caused its surface, shift from hydrophilic to hydrophobic and then to super hydrophilic region. Abstract: Nanofinished aluminum alloys are widely used in optics as metallic mirrors, micro-electronics and micro-mechanical assemblies. In general, the ductile materials like aluminum and copper are being machined by diamond turn machining (DTM) process to get the nanometric surface finish. However, it is impossible to achieve an atomic level surface finish by conventional random finishing processes like lapping. With a newly developed chemo mechanical magnetorheological finishing (CMMRF) process, an experimental investigation has been carried out on Al-alloy by implementing suitable chemical reactions on the superficial layer of the workpiece. A full experimental design has been performed to optimize the process by varying several parameters such as concentration of chemicals, concentration of abrasives, concentration of carbonyl iron particles and working gap. Effect of different parameters has been studied an average surface roughness value (Ra) of less than 2 nm was achieved, which was further improved by optimizing the process parameters. The best result of CMMRF finished aluminum (0.597 nm) was way better than DTM and chemo-mechanical polishing process. In terms of reflectance, in the range of 300–2200 nm the processed surface was found to have 5% higher value in comparison with sputtered counterpart. Also, it was observed that finishing of aluminum caused its surface to shift from hydrophilic to hydrophobic and then to the super-hydrophilic region with a contact angle of 16°. By this experimentation, more than 98% improvement on surface finish has been observed. Therefore, it has been concluded that the CMMRF process can finish aluminum alloy of the order of few angstrom (Å).